Development and decay of procedural skills in surgery: A systematic review of the effectiveness of simulation-based medical education interventions. Issue 4 (August 2021) - Higgins, Mark; Madan, Christopher; Patel, Rakesh
Abstract: Context: Changes to surgical training programmes in the UK has led to a reduction in theatre time for trainees, and an increasing reliance on simulation to provide procedural experience. Whilst simulation offers opportunity for repetitive practice, the effectiveness of simulation as an educational intervention for developing procedural surgical skills is unclear. Methods: A systematic literature review was undertaken to retrieve all studies describing simulation-based medical education (SBME) interventions for the development of procedural surgical skills using the MEDLINE, PsycINFO, CINAHL, EMBASE and PUBMED databases. Studies measuring skill retention or demonstrating transferability of skills for improving patient outcomes were included in the review. Results: SBME is superior to no training and can lead to improvement in procedural surgical skills, such that skills transfer from simulated environments into theatre. SBME results in minimal skill degradation after 2 weeks, although more significant decay results after >90 days. Many studies recruited <10 participants, used a variety of methods and were restricted to endoscopic surgical techniques. All studies did not compare interventions with non-SBME teaching methods for developing procedural surgical skills. No studies compared the curriculum design of different surgical training programmes. Conclusions: SBME interventions are effective for developing procedural skills in surgery. SBME interventions are also effective for preventing the decay of procedural surgical skills. Although no studies demonstrate non-inferiority of SBME interventions compared to time in theatre developing skills, SBME interventions do enable the transfer of skills into theatre, and the potential for improving patient outcomes.